Dampak Pengembangan Obyek Wisata Pantai Pasir Putih Situbondo Terhadap Kesempatan Kerja - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT: In recent years tourism has become one of the choices of economical development in many developed countries and it is also the best way to generate foreign exchange as well as job oppomunity and other benefit. Pasir Putih Beach is one of famous place tourism in East Java that was developed from government to expand the economic and social activities. Tourism development impacts many kinds of activities and opportunity for local communities in new jobs and businesses, additional income, new markets for local products, transfer of knowledge and technology. The aimed of this study to describe the tourism development policy inconnection with job opportunity and social cultural aspect in the Pasir Putih Beach destination.